Cladonia galindezii, a new Antarctic lichen species - Øvstedal, Dag Olav (Cryptogamie, Bryologieet Lichénologie, 1988)
Keywords: Antarktis; botanikk; lav; planter

On the variation of Ochrolechia parella in the western Antarctic and Subantarctic area - Øvstedal, Dag Olav (Polarforschung, 1988)
Keywords: Antarktis; botanikk; lav; planter

Some lichens from HU Sverdrup Mountains, Dronning Maud Land, Antarctis - Øvstedal, Dag Olav (Nova Hedwigia: Zeitschrift fur Kryptogamenkunde, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

A new Pannaria species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cryptogamie, Bryologie, Lichenologie, 1983)
Pannaria austro-orcadensis Ovst., sp.nov., from the northern maritime Antarctic, is characterized by its purple-brown lobulate thallus, brown apothecia smooth spores and no secondary products. It grows on moist gravelly soil and bryophytes.
Keywords: Dronning Maud Land; botanikk; lav; planter